Persepsi Lansia Mengenai Kelompok Senam Lansia Di Desa Sukawati, Kecamatan Sukawati, Kabupaten Gianyar - Komang Srititin Agustina (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2022)
Elderly is an age group that is vulnerable to changes in conditions and situations caused by physical, psychological and social changes. Sukawati village developed an elderly gymnastics group to maintain the health of the elderly. However, only a small proportion of the elderly in Sukawati Village participated in the elderly gymnastics group. This study uses a qualitative descriptive method which aims to obtain in-depth information about the elderly's perception of their attitudes and behavior towards the elderly gymnastics group. The number of respondents in this study were 6. Sampling using purposive sampling technique. Data were collected through in-depth interviews, in which the researcher himself became the instrument. The information from the interviews was then processed manually and analyzed thematically. This study found that the perception of the factors that encourage the elderly to join the elderly gymnastics group is because they feel that they get benefits from participating in their activities. The perceived benefits include feeling healthier, sleeping better, and being able to socialize with elderly friends. The perception of the factors that hinder the elderly from participating in the activities of the elderly gymnastics group is that they feel they are healthy, work, and traditional activities